Phosphorus–nitrogen compounds. Part 65. Novel diansa-spiro-cyclotetraphosphazenes: synthesis, characterization, bioactivity and electrochemical properties, and dye-sensitized solar cell fabrication studies. (15th September 2022) - Mutlu, Gürcü; Okumuş, Aytuğ; Elmas, Gamze; Kılıç, Zeynel; Güzel, Remziye; Sabah, Büşra Nur; Açık, Leyla; Mergen, Hatice; Hökelek, Tuncer
Abstract : The syntheses, structural, stereogenic and electrochemical properties, dye-sensitized solar cell fabrication, antimicrobial, cytotoxic and DNA-binding activities of mono-ferrocenyl-2, 4-ansa -6, 8-ansa-spirocyclotetraphosphazenes were studied. Abstract : In this investigation, the substitution reaction of octachlorocyclotetraphosphazene, N4 P4 Cl8 (tetramer, OCCP, 1 ), with sodium 3-( N -ferrocenylmethylamino)-1-propanoxide (L1 ) was found to yield the compounds, 2, 4-ansa -(2 ) and spiro -(2 ) cyclotetraphosphazene derivatives. The starting hexachloro-2- cis -4-dichloro-monoferrocenyl-ansa-(N/O)cyclotetraphosphazene (2 ) reacted separately with dipotassium salts of N2 O2 donor-type aminopodands, (KOPhCH2 NH)2 R [R = (CH2 ) n, n = 2 (L2 ) and n = 3 (L3 )], to produce mono-ferrocenyl-2, 4-ansa -6, 8-ansa-spirocyclotetraphosphazenes (dias ; 3 and 4 ). Both products were purified by column chromatography, and their structures were confirmed using ESI-MS, FTIR, 1 H, 13 C, and 31 P NMR spectral data. Besides, the molecular and crystal structures of 4 were elucidated by single-crystal X-ray diffraction. Compound 4 has four-different chiral P-centers. However, the absolute configuration of stereogenic P-centres of an enantiomer was designated as SS ′ S ′′ R ′′′. Both new compounds were also used for the examination of optical and electrochemical properties, and survey of bioactivity. To this end, the minimum inhibitory, bactericidal, and fungicidal concentrations (MIC, MBC, and MFC) were determined with the microdilution technique. These MIC, MBC, and MFC values were found to vary between 2500 μM and 312.5 μM. DNA cleavage activities of 3 and 4 with pBR322 plasmid DNA were also studied using electrophoretic mobility on an agarose gel. Bam HI and Hind III restriction enzyme digestions of compound-pBR322 plasmid DNA were conducted to supply more insight into changes in DNA conformation. Cyclotetraphosphazene 4 caused DNA cleavage activity even at the lowest concentration. In addition to that, compound 4 inhibited enzyme digestion, indicating that DNA binds to A/A nucleotides with DNA binding activity. Moreover, the cytotoxicities of 3 and 4 were investigated by MTT assay against MDA-MB-231 breast cancer cells and COS-1 mammalian fibroblast cells. On the other hand, the optical and electrochemical properties of dias 3 and 4 were studied using UV-vis absorption and cyclic voltammetry techniques. As a result, both compounds can be suggested as ferrocene-based charge transformable phosphazene structures that can be used as new generation and synergistic DSSC materials.